Glucocorticoid stimulation induces regionalized gene responses within topologically associating domains - Tav, Christophe; Fournier, Éric; Fournier, Michèle; Khadangi, Fatemeh; Baguette, Audrey; Côté, Maxime C.; Silveira, Maruhen A. D.; Bérubé-Simard, Félix-Antoine; Bourque, Guillaume; Droit, Arnaud; Bilodeau, Steve (Frontiers in Genetics, 2023)
Transcription factor binding to cis-regulatory regions regulates the gene expression program of a cell, but occupancy is often a poor predictor of the gene response. Here we show that a glucocorticoid stimulation led to a reorganization of transcriptional coregulators MED1 and BRD4 within topologically associating domains (TADs), resulting in active or repressive gene environments. Indeed, we observed a bias towards activation or repression of a TAD when their activities were defined by the number of regions gaining and losing MED1 and BRD4 following a dexamethasone (Dex) stimulation. Variations in Dex-responsive genes at the RNA levels were consistent with the redistribution of MED1 and BRD4 at the associated cis-regulatory regions. Interestingly, Dex-responsive genes without differential recruitment of MED1 and BRD4 or binding by the glucocorticoid receptor (GR) were found within TADs which gained or lost MED1 and BRD4 suggesting a role of the surrounding environment in gene regulation. However, the amplitude of response of Dex-regulated genes was higher when differential recruitment of GR and transcriptional coregulators was observed, reaffirming the role of transcription factor-driven gene regulation and attributing a lesser role to the TAD environment. These results support a model where a signal-induced transcription factor induces a regionalized effect throughout the TAD, redefining the notion of direct and indirect effects of transcription factors on target genes.